A Novel Iterative Water Refraction Correction Algorithm for Use in Structure from Motion Photogrammetric Pipeline - Skarlatos, Dimitrios; Agrafiotis, Panagiotis (My University, 2018)
Photogrammetry using structure from motion (SfM) techniques has evolved into a powerful tool for a variety of applications. Nevertheless, limits are imposed when two-media photogrammetry is needed, in cases such as submerged archaeological site documentation. Water refraction poses a clear limit on photogrammetric applications, especially when traditional methods and standardized pipelines are followed. This work tries to estimate the error introduced to depth measurements when no refraction correction model is used and proposes an easy to implement methodology in a modern photogrammetric workflow dominated by SfM and multi-view stereo (MVS) techniques. To be easily implemented within current software and workflow, this refraction correction approach is applied at the photo level. Results over two test sites in Cyprus against reference data suggest that despite the assumptions and approximations made the proposed algorithm can reduce the effect of refraction to two times the ground pixel size, regardless of the depth.
Keywords: Two-media photogrammetry; Bathymetry; Refraction correction; Structure-from-Motion; Multi-view stereo; LiDAR